2019
DOI: 10.1101/2019.12.18.881755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The human telomeric nucleosome displays distinct structural and dynamic properties

Abstract: ABSTRACTTelomeres protect the ends of our chromosomes and are key to maintaining genomic integrity during cell division and differentiation. However, our knowledge of telomeric chromatin and nucleosome structure at the molecular level is limited. Here, we aimed to define the structure, dynamics as well as properties in solution of the human telomeric nucleosome. We first determined the 2.2 Å crystal structure of a human telomeric nucleosome core particle (NCP) containing 145 bp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…6a, e ). Previous SAXS and biochemical assay studies suggested that the telomeric NCP exhibits overall higher mobility in comparison with other canonical NCPs 22 . In addition, as discussed in the below section, our SSNMR data illustrates that the hH3 and hH4 N-terminal tails possess higher degree of flexibility in the telomeric NCP compared with the Widom 601 NCP.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…6a, e ). Previous SAXS and biochemical assay studies suggested that the telomeric NCP exhibits overall higher mobility in comparison with other canonical NCPs 22 . In addition, as discussed in the below section, our SSNMR data illustrates that the hH3 and hH4 N-terminal tails possess higher degree of flexibility in the telomeric NCP compared with the Widom 601 NCP.…”
Section: Resultsmentioning
confidence: 92%
“…The critical roles of telomeres in protecting chromosomes urge the comprehensive elucidation of the structure and dynamics of telomeric nucleosomes to understand the molecular foundations of its unique biological behavior and function. A recently published study solved the XRD structure of a NCP reconstituted from 145 bp TTAGGG human telomeric sequence, and revealed a structure very similar to other NCPs with canonical DNA sequences, but an overall less stable complex in solution 22 . These unique dynamic properties seem to contribute to the biological activities of telomeric nucleosomes.…”
Section: Introductionmentioning
confidence: 88%
“…The 13 C-13 C correlation spectra of telomeric and 601-NCP overlay remarkably well as illustrated in Figure 44 and Figure 45 for hH4 and hH3 globular domains respectively. Overall, hH4 and hH3 globular domains in the telomeric NCP have the same confirmation as in the 601-NCP, congruent with the recently published high-resolution X-ray structure of telomeric NCP (Soman, Liew et al 2020). However, a few stretches in the telomeric NCP exhibited minor conformational differences, particularly in side-chains as evidenced by the deviations in chemical shifts of A38, V43-S47, K79-T80, and R95-T96 in hH4 (highlighted in Figure 46), and Y54, T80, and I130 in hH3 (highlighted in Figure 47C).…”
Section: Structure and Dynamics Of Histone H4 And H3 Globular Domainssupporting
confidence: 89%
“…However, the first high-resolution X-ray crystallography structure of NCP with the human telomeric DNA of TTAGGG repeat has been recently published by our colleagues (Soman, Liew et al 2020). The important outcome of this study is that telomeric NCP can be crystallized despite the challenges caused by the weak positioning of telomeric DNA to the octameric core.…”
Section: Ssnmr Study Of H3 N-terminal Tail In the Ncpmentioning
confidence: 91%
See 1 more Smart Citation